Finding oneself? Contemplating on paintings with a religious theme in clinical pastoral care - F. Herm; V. Kessler; E. Kloppers (Acta Theologica)
This article is based on intra- and interdisciplinary explorative research on contemplating art with a religious theme in the context of clinical pastoral care. The study, done in a rehabilitation hospital in Bavaria, Germany, explores the emotions, feelings, and thoughts aroused by contemplating on Rembrandt’s painting, The return of the prodigal son. It includes guided observations of the painting, voluntary feedback on forms, and eight interviews on what could be observed under the aspects of self-reflection, identification, and reorientation. Aspects of aesthetics, biography, religion, and emotion are also observed. The evaluation of the aesthetic reception shows two types of reactions, namely identification with a person or a theme of the painting. It is observed that self-reflection, an important factor for reorientation during the process of clinical pastoral care, is present in all interviewees. Each interviewee presents an individual characteristic related to their life situation. Core themes corresponding to the painting’s content are guilt, forgiveness, mercy, and reorientation. The practice of contemplation on paintings with a religious theme, using methods common in the social sciences and empirical theology, represents one possibility among many in the field of clinical pastoral care. The study provides new information on the therapeutic possibilities of creative experiences, by contemplating on paintings that can be explored further.